The study on the main economic activities in Romania - Alesandra Marina Manolache (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
The present paper proposes the analysis of the sectors of the national economy from the point of view of production (Gross Domestic Product) but also from the point of view of consumption (average monthly labor costs). This paper is based on the analysis of the statistical data from a quantitative and qualitative point of view, in order to be able to raise awareness of the current level and the evolutions of the sectors and economic branches of Romania in the formation of GDP, but also in terms of labor productivity and labor cost. Finally, a comparison will be made between labor productivity (from a value point of view) and labor costs, and on the other hand it will analyze the value of the agricultural branch in order to determine the influence of this productivity / cost ratio on the value of production.
Keywords: N10; Q16; 330; agriculture; economic activities; evolution